Analyzing Determinant Components on East Java Rice Surplus Contribution Using Dynamical System Approach - Kuntoro Boga Andri; Nugraha Pangarsa (Hasanuddin University, 2016)
The Ministry of Agriculture has proclaimed rice as a main food commodity, beside corn, soybeans, meat and sugar. In order to achieve the target of the Ministry of Agriculture, East Java provincial government has stipulated a policy, focusing on rice surplus of 5 million tons in 2014. This attempt is to reach the surplus number through a wide selection of technological innovations (determinant component) that increases the productivity of rice (New Superior Variety/VUB, Site Specific Nutrient Management/SSNM, Integreted Crop Management/ PTT, Jarwo/double row planting system, balanced fertilization, SOP harvest / postharvest), as well as an increase in Planting Index/IP by improving irrigation and food diversification program. By using a dynamical system approach (modeling), it can be measured the contribution of each determinant components in achieving surplus / rice self-sufficiency through simulation. The results of the simulation, it was known that the East Java’s rice surplus will continue to decline from 1,806,282 tons (2014) with 170% self-sufficiency index, fell to 1.706.771 tons (2017) and would be 1.367.901 tons (2025). This condition is due to the increasing number of population, agricultural area continues to shrink and productivity is relatively fixed. Index sufficiency / surplus will increase if there is an interference of educational policy to implement a massive exceed of VUB, SSNM, PTT, Jarwo, balanced fertilization, SOP harvest / post-harvest, IP increasing and the succession of diversification in East Java. A surplus of 4.7 million tons of rice in 2014 within East Java can be achieved by implementing massive educational policy movement of PTT and VUB (100% of the area), the application of SOP harvest / post-harvest to reach at least 50% of the area of paddy and controlling OPT strictly. The highest self-sufficiency index (281%) and a surplus of 5.22 million tons will be achieved in case of an interference in implementing policy of PTT jarwo (100% of the area) and an IP increasing amounted to 1.0 (additional areas that can be irrigated, 33.000 ha). Sustainable rice surplus would be achieved in case of an attempt to make food diversification program completely successful, strengthen family planning programs and strictly guard the Regulation No. 5/2012 on the minimum acreage of paddy fields that must be maintained.